Intravitreal Bevacizumab for Pseudophakic Cystoid Macular Edema; a Systematic Review - Ghasemi Falavarjani, Khalil (Ophthalmic Research Center, 2012)
Cystoid macular edema (CME) is a major cause of decreased vision after complicated or uncomplicated cataract surgery. This paper reviews the use of intravitreal bevacizumab (IVB) injection for treatment of pseudophakic CME. In a literature search of all articles available on Medline and Scopus databases, 11 studies including one prospective and 4 retrospective studies, 4 case reports, one letter to editor and one review article were identified. All articles except one, reported the use of IVB for chronic CME unresponsive to at least one conventional treatment modality. The level of evidence for all studies was categorized as low or very low. Although intravitreal bevacizumab might be effective for many cases of pseudophakic CME, its use should be reserved for eyes unresponsive to conventional treatment modalities.